Folkelig idræt kan ikke sådan måles eller vejes' - Om festjournalistik eller: Hvordan rapporterer man ikke-olympisk mangfoldighed? - Eichberg, Henning (Forum for Idræt, 2003)
Med DGI's landsstævne 2002 som eksempel beskriver og diskuterer artiklen de journalistiske udfordringer og problemer ved at rapportere fra en festivalpræget idrætsbegivenhed. “Popular sport cannot be weighed and measured”. On festival journalism, or How to report non-Olympic variety Sport journalism has a “post-modern” problem. Since the end of the twentieth century, an event culture has developed where media strategies and interests of sale, technologies of visualisation, political interests and popular fascination join in the great show of entertainment. The latemodern festival culture does not only embrace the Olympic Games but it also influences festivals which have grown out of quite different traditions such as the German Turnfest and the Danish landsstævne of popular gymnastics and sports. The ways in which the media react to sport as festivity is here analysed for the case of Landsstævne 2002 on Bornholm. Besides the dominant journalism of records, we find a journalism of ersatz records and of the spectacular, problem journalism side by side with a journalism of joyful faces, human interest journalism and show journalism as well as attempts at political and cultural journalism. The different ways of reporting the festival of popular culture confront some fundamental questions about the relation